Obesity: dietary treatment - Steer, T; Jebb, S (2004)
Dietary treatment of obesity should aim to reduce the risk of chronic disease. This involves reductions in energy intake to facilitate weight loss together with other changes in the composition of the diet to further decrease health risks. Assessing habitual food intake can provide useful qualitative information on a woman's eating habits. In general terms, advice should be given on reducing dietary fat, increasing unrefined carbohydrates, fruits and vegetables and avoiding too many high-fat/high-sugar foods. However, careful assessment of an individual's background such as lifestyle, motivation, treatment expectations and previous dieting history is essential to tailor dietary advice to individual needs. Broader aspects of eating behaviour should also be considered including reductions in portion size, and developing a structured meal pattern. Meal replacement products are a useful aid to adherence for some individuals and in clinical trials have been shown to enhance weight loss. Unorthodox or 'fad' diets often promise dramatic short-term results. Frequently they are nutritionally unbalanced and there is no evidence to suggest they assist long-term weight control and reduced risk of chronic disease. The role of pharmacotherapy and bariatric surgery in weight loss and the implications for dietary advice are also discussed. © 2004 Elsevier Ltd. All rights reserved.